(untitled) (Journal of Science and Technology, 2016)
Cashew (Anacardium occidentale L.) has become a very important non-traditional tree crop in Ghana, with increasing area of cultivation and nut yield. An important threat to the sustained production of the crop is the cashew mosquito, Helopeltis schoutedeni. Petri dishes laboratory bioassay was carried out with different rates of Karate, Cyperdim and Confidor on the 5th instar nymphs and adults of H. schoutedeni, to determine a suitable insecticide and its minimum effective dosage to control this insect. Field experiments were also conducted to determine the efficacy and persistence of Karate and Cyperdim on H. schoutedeni. In the laboratory bioassay, Karate and Cyperdim were found suitable with minimum effective dosages as 0.010% and 0.102% active ingredient (a.i.), respectively. The mean corrected mortality recorded for the minimum effective dosages of the two insecticides on the 5th instar nymphs and adults was more than 95% in the bioassay. The persistence tests indicated that, one day after insecticide application, both Karate and Cyperdim gave 100% kill. Seven days after treatment, only the Cyperdim killed more than 95% of the insect. From 14 days after treatment, there was a marked reduction in the percentages killed and the differences were no longer significant between the two insecticides, although the Cyperdim still gave higher per cent kill. From the results, either Karate or Cyperdim can be used in the case of a massive invasion of a cashew farm by the pest, to knock them off. But on prophylactic basis Cyperdim would be a better choice as it showed longer persistence than Karate.